(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: A thorough understanding of human anatomy is fundamental for nursing students to provide effective patient care. This paper highlights the key anatomical systems that nursing students should prioritize, including the cardiovascular, respiratory, nervous, musculoskeletal, and digestive systems. The study also emphasizes the importance of integrating anatomical knowledge with clinical practice to enhance patient assessments, diagnostics, and treatments.